Event-Based Frequency Detection Methods for Determining Wingbeat Frequencies of Honey Bees - Harrington, Kalonji; Taeckens, Elijah A.; Tremba, Matthew; Lynch, Matthew; Fatima, Ayman; Kukadia, Riya; Majumder, Zain; Mathur, Rohan; Park, Daniel; Strucko, Richard; Traska, Stefan; Horiuchi, Timothy K. (Conference proceedings : Midwest Symposium on Circuits and Systems, 2024)
Event-based vision sensors offer high-speed, low-latency vision solutions. The sensitivity of these sensors to temporal-changes make them ideal for applications involving rapidly-moving subjects or patterns. This work demonstrates the use of an event-based vision sensor to real-time detection of wing-beat frequency in flying honey bees. Wing-beat frequency measures are useful for species identification or colony health monitoring applications. A number of potential methods for detecting the wing-beat pattern are explored and assessed for the given problem. The results show that event-based vision can reliably measure the wingbeat frequency of bees in real time.